Geriatric Nephrology OSCE: Managing Drugs With Aging Patients and Kidneys - Brahm Vasudev; Deborah Simpson; Emily Haines; Edmund Duthie; Christopher Anderson; Kathryn Denson (Association of American Medical Colleges, 2015)
Abstract Introduction At the Medical College of Wisconsin, geriatricians, nephrologists, and medical educators worked together to create and implement a geriatric nephrology objective structured clinical examination (OSCE) for nephrology fellows. Key curriculum content gaps (pathophysiology of the aging kidney, medication and renal dosing, and renal toxicity in elderly patients) were identified through a needs assessment including ACGME nephrology requirements, nephrology fellows' in-service exam scores, survey of fellows and faculty to identify areas of perceived weakness, literature review, and brief multiple-choice questions of basic science linked to clinical case questions. Methods Curriculum content was delivered using the OSCE educational method. The curriculum session highlighted kidney injury and pharmacology topics: drug toxicity and underlying science through an OSCE session with postsession debriefing provided by faculty. Fellows were evaluated by faculty using a checklist, and fellows evaluated the session prior to the end. Results The OSCE curriculum session (N = 6) showed strong learner evaluations (1 = poor, 7 = excellent), including "Session objectives were clearly stated and accomplished" = 6.8, "Feedback provided in debriefing will improve my ability to care for geriatric patients" = 5.8, and "Overall effectiveness of session in improving my ability to care for geriatric patients" = 6.5. Discussion Fellow performance from the OSCE rater checklists completed by faculty and standardized patients showed the fellows' extent of completion/inclusion of OSCE elements to range between 69% and 80% complete. The program director identified a discrepancy between fellows' knowledge and some communication skills in summarizing the information and providing closure to the session. The ability of the OSCE to provide direct observation of the fellows' performance was highly valued by the program director and has led to further adjustments in teaching and assessment over time.